Pemanfaatan Limbah Botol Plastik sebagai Produk Ramah Lingkungan dan Bernilai Ekonomi melalui Inovasi Tempat Pensil “ReBloom” - Yuyun Setyawati; Ezar Nafis Bramantara; Muhammad Romadhoni Adi Setiawan; Muhammad Yasin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The problem of plastic waste in Indonesia is increasingly urgent as plastic consumption increases and sustainable management is lacking. This research aims to explore the potential of utilising plastic bottle waste as a creative and environmentally friendly product in the form of